Description the completeness of prescriptions for inpatients at the Pharmacy Installation HKBP Balige General Hospital period of July 2020 - Devi Yanthre Sari Manurung; Baharuddin J.E.A Togatorop; Fepri Gunawan Tampubolon (International Journal of Health Engineering and Technology, 2023)
Prescription is a written request from a doctor to a pharmacist to provide drugs for patients written in the prescription. For in accordance with applicable laws and regulations to minimize irrational use of drugs and preventmedication errors for patient safety purposes. The purpose of this study was to describe Description the completeness of prescriptions for inpatients at the Pharmacy Installation HKBP Balige General Hospital period of July 2020. The design of this study was descriptive, with a sample of 186 prescriptions, using a cluster random sampling technique. The results showed that 46.2% of prescriptions at the Balige HKBP RSU for the July 2020  period were complete and 53.8% incomplete. Of the total 186 prescription sheets, the information on the doctor's name (27.4%), the doctor's initial (5.9%), the patient's name (0.5%), the patient's address (36.6%), the instructions for use (10,2%). This shows that the completeness of the recipe at RSU HKBP Balige is not complete. Incomplete prescriptions occur because many visiting patients increase the busyness of the prescriber, so doctors do not have time to write a complete prescription. It is recommended to the management of RSU HKBP Balige to put more emphasis on doctors to complete prescriptions, so that TTK does not find incomplete prescriptions anymore.